Propaganda, cooperativismo e recepção : apropriações e sentidos construídos por telespectadores dos filmes publicitários do Sicredi - Motta, Taís Flores da (Universidade do Vale do Rio dos Sinos, 2011)
This research investigates the reaction of the advertising film fromSicredi, seeking to understand the denotations offered and appropriations made by users in relation to cooperativism, and the role of the economic culture, cooperative culture and mediatic competencies in this process. To substantiate the investigation, I have worked with mediatization concepts and problematic related to the creation of meaning, on the addressing and characteristics of the advertising film to think about the investigated product. For the reaction, I have worked with the concept of mediation, appropriation, consume and the production of meaning, and I have also substantiated the mediations investigated. Regarding the methodological strategies, they were guided by a multi-methodological perspective. In the context of the product, I analyzed a corpus composed of threeSicredi commercials, seeking to identify the denotations of cooperativism offered in these films, as well as the data related to the production of the campaign collected through interviews with the institutional communication coordinator ofSicredi. In the context of reaction, I performed an exploratory search using a sample of four viewers ofSicrediadvertisements, and a systematic search using four different subjects related to the investigatedmediations. As for data collection I developed a number of methodological procedures that includedinterviews within a historical perspective, observation, and video-conversation and a socioeconomic questionnaire. In the survey results we can see how the mediatization configured and altered the ways of communication in the field of cooperativism, the relationship of cooperative organizations with partners and other people; howSicrediappropriated the strategies of conventional advertising to convey the values and characteristics of cooperativism in their commercials; appropriations realized and how the media chosen shape the production of meaning of the interviewees in relation to the cooperativism offered by advertising films.
Keywords: Cooperativismo; Filme publicitário; Midiatização; Recepção; Cooperativism; Advertising; Mediatization; Reception; ACCNPQ::Ciências Sociais Aplicadas::Comunicação